2010
DOI: 10.1016/j.heares.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Noise-induced hearing loss alters the temporal dynamics of auditory-nerve responses

Abstract: Auditory-nerve fibers demonstrate dynamic response properties in that they adapt to rapid changes in sound level, both at the onset and offset of a sound. These dynamic response properties affect temporal coding of stimulus modulations that are perceptually relevant for many sounds such as speech and music. Temporal dynamics have been well characterized in auditory-nerve fibers from normal-hearing animals, but little is known about the effects of sensorineural hearing loss on these dynamics. This study examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 64 publications
(106 reference statements)
9
37
2
Order By: Relevance
“…Gunshot noise trauma delayed guinea pig CAPs by ∼50-200 μs compared with controls (13). Conversely, other studies found reduced latencies of single AN fibers in response to acute noise (28,30,31,35). Latency reductions are probably due to the particular mammalian cochlea mechanical tonotopy and tuning properties.…”
Section: Discussionmentioning
confidence: 84%
“…Gunshot noise trauma delayed guinea pig CAPs by ∼50-200 μs compared with controls (13). Conversely, other studies found reduced latencies of single AN fibers in response to acute noise (28,30,31,35). Latency reductions are probably due to the particular mammalian cochlea mechanical tonotopy and tuning properties.…”
Section: Discussionmentioning
confidence: 84%
“…For subjects in the mid and high threshold groups, poor detection efficiency does not necessarily indicate a deficit of the central auditory system but may suggest a peripheral degradation of important cues that cannot be resolved by the central detector. The degree to which detection efficiency is compromised by peripheral degradation of detection cues is unknown, as are the sources of this degradation; however, these sources may be related to poorer frequency resolution (e.g., Sellick et al 1982) or altered neural adaptation (Scheidt et al 2010). Peripheral degradation of detection cues may also contribute to increased individual differences among hearing-impaired listeners, as compared to normal-hearing listeners, in TMCs and other psychophysical and speech perception tasks (e.g., Moore 2007).…”
Section: Sensitivity To Kmentioning
confidence: 99%
“…Because cochlear hearing loss is associated with broadening of peripheral auditory filters due to the loss of cochlear gain, the effect of hearing loss on the cochlear latency-frequency function should be similar to the effect of a high stimulus level. A recent physiological study by Scheidt et al (2010) reported that response latencies in the AN of anesthetized chinchillas with noise-induced hearing loss were shorter than those in the normal-hearing animals, but only in fibers that showed broader tuning in addition to threshold elevation after the noise exposure. The decrease in latency was about 0.5 ms, similar to that shown by the postmortem data in the study by Ruggero and Temchin (2007).…”
Section: Perceived Across-frequency Synchrony and The Cochlear Latencmentioning
confidence: 97%
“…Unfortunately, the hearing loss in the study by Scheidt et al (2010) was induced using a bandpass noise extending from 1 to 4 kHz, and thus, thresholds were elevated over a limited frequency range that did not include CFs below 1 kHz. For humans, the latency-frequency functions estimated from derivedband ABRs measured in the study by Don et al (1998) suggest that hearing loss in the apical region results in a greater decrease in response latency than that in the basal region of the cochlea.…”
Section: Perceived Across-frequency Synchrony and The Cochlear Latencmentioning
confidence: 99%
See 1 more Smart Citation